DETECTION OF FECAL INDICATOR BACTERIA IN SHIP BALLAST WATER - Elcicek, Huseyin; Cakmakci, Mehmet (YILDIZ TECHNICAL UNIV, 2016)
Nowadays, discharge of ballast water is recognized as one of the greatest threats to the biodiversity of Sea of Marmara. In addition, transfer of pathogenic bacteria from ships' ballast water to ecosystem and coastal waters of Marmara Sea has negative impacts. In this study, presence of fecal indicator bacteria (FIB) and Salmonella spp. were investigated in the ships' ballast water coming from different marine environments of Burgas-Bulgaria, Susa-Tunisia and Misratah-Libya to Marmara Sea. Membrane filtration method was used for the detection of FIB and Salmonella spp. in the samples. Based on the experimental results, presence of fecal indicator bacteria and Salmonella spp. were found to be over the International Maritime Organization (IMO) limit values. It is concluded that the uptake of ballast water from these areas and discharging to Marmara Sea could pose a serious threat to the coastal ecosystems and human health. Thus, development of national ballast water management procedure is urgently needed, especially for the future of the Marmara Sea.
Keywords: Ballast water; fecal indicator bacteria; Salmonella spp.; Marmara Sea; PATHOGENIC BACTERIA; SALMONELLA; PREVALENCE; SEA; GASTROENTERITIS; MICROORGANISMS; CAMPYLOBACTER; ENVIRONMENT; POLLUTION; BEACH; Engineering